Systematic Literature Review On It Asset Management Framework In Security Operation Center - A’in Hazwani Ahmad Rizal; Sakinah Ali Pitchay; Yau Ti Dun (KUIS, 2024)
Each successful cyber incident cost $4.24 million per incident on average in 2021 which impacted the company's reputation, (IBM, 2022). The growing cybersecurity threats have affected business environments in all different sectors, especially in the IT landscape. Deploying a Security Operation Center (SOC) either in-house or outsourced concepts would be one of the mitigations to prevent cybercriminals. SOC operates in a huge team that relies on people, processes, and technology. However, 60% of Malaysian cybersecurity technologies are currently deploying outdated versions according to the latest findings, (Digital News Asia, 2022) and there is an inadequate tool used in SOC environments. Moreover, there is still a gap in the SOC framework used in maintaining the quality of technology, especially IT assets, (John Burke, 2020). This paper aims to analyze the state-of-the-art IT asset management policy used globally via a comparative study. It employs qualitative research on the literature surveys for SOC's existing IT asset management. The findings from the analysis show that existing frameworks are inadequately guided especially in maintaining the IT assets' quality which is aligned with the current technology. By proposing an improved policy in IT asset management in SOC, the cybersecurity threat prevention and identification process could be improved. Thus, this paper will help in identifying a comprehensive IT asset management in SOC and the total cost damage which aligns with governance’s initiative nation cybersecurity strategy for 2020-2024